Public preferences for a payment for ecosystem services scheme to conserve forest: a choice experiment approach - Ya'cob, Mohd Rusli; Mamat, Mohd Parid; Abdullah, Mukrimah; Matthew, Nitanan Koshy; Sanusi, Faizah (Eternal Scientific Publications, 2023)
The conceptualization of Payments for Ecosystem Services (PES) is essential for sustainable financing mechanisms for the provision of environmental goods and services. Through the goal of PES programs, sustainable forest management can be achieved by securing forest-derived benefits to support conservation and sustainable livelihoods. Ultimately, PES development is one of the centers of attention of policymakers in Malaysia to fulfill the demands and concerns of a global community by managing the forest with a stronger focus on conservation and environmental protection. A Choice Experiment was conducted among 375 respondents in Terengganu to elicit their preferences for the presented attributes of the proposed PES program. Several attributes are proposed namely, Forest Landscape (FL), Flood Control (FC), Biodiversity of Fauna (BF), Recreational Facilities (RECC), Community Participation (COMM) and donation for annual conservation fees (PRICE). The conditional logit and mixed logit models were used for the analysis of the data, which were gathered between May and September of 2022. The findings revealed that the respondents are willing to pay significantly per year to improve the attributes of ecosystem services in Gunung Tebu Forest Reserve (GTFR), Terengganu, Malaysia. This finding shows that PES is a promising program to support forest conservation efforts. This study also enlightens the direction for policymakers to develop the future PES program to support forest conservation.